The palenque of Guachipa (1713). Some aspects of maronnage on the outskirts of Lima (Peru) - Tardieu, Jean-Pierre (2018)
Apparently, the actions in 1713 of the maroons of Guachipa, near Lima, did no differ from the well-known behavior of their predecessors. Nevertheless, the consideration of the judicial documents about the repression highlights the tensions for the power in the palenque, due to the confrontation of two ethnic blocks. The testimonies emphasize the character of the leader, who knew how to handle himself with intelligence, but also with humanity. Moreover, the plea of the defence of the accused, well ahead of his time in denouncing the inconsistencies of slavery and appealing to the natural right of freedom, is very striking.